Towards Building Reuse-Based Digital Libraries for National Universities in Patagonia - Cechich, Alejandra (2018)
This article presents a case study exploring the use of software product lines and reference models as mechanisms of a reuse-based design process to build digital libraries. As a key component in a modern digital library, the reference architecture is responsible for helping define quality of the resulting repository. It is true that many efforts have been addressed towards providing interoperability; however, repositories are expected to provide high levels of reuse too, which goes beyond that of simple object sharing. This work presents the main steps we followed towards building a reusable digital library capable of accommodating such needs by (i) providing mechanisms to reuse resources, and (ii) enabling explicit sharing of commonalities in a distributed environment.